Pengaruh Pengungkapan Kinerja Lingkungan, Green Intellectual Capital, dan Profitabilitas Terhadap Nilai Perusahaan - Yeni DwiAgustin (Fakultas Ekonomi dan Bisnis, 2026)
This study aims to analyze the effect of environmental performance disclosure, green intellectual capital, and profitability on firm value, with the Covid-19 pandemic as a control variable, in transportation and logistics companies listed on the Indonesia Stock Exchange during the 2019–2023 period. This study uses a quantitative approach with secondary data. The study sample consists of 18 companies with a total of 90 observations, selected using a purposive sampling technique. Data analysis was performed using panel data regression with the Random Effect Model (REM). The results show that environmental accounting has no effect on firm value. Green intellectual capital has a negative effect on firm value, whereas profitability has a positive and significant effect on firm value. Simultaneously, the three independent variables significantly affect firm value. This study concludes that profitability remains the primary factor considered by investors in enhancing firm value, while the disclosure of environmental aspects is not yet a primary consideration in investment decisions.
Finalisasi Maya 12/08/2026
Keywords: environmental disclosure; environmental performance; environmental performance disclosure; green intellectual capital; profitability; firm value; Covid 19.